PENGARUH PRODUCT KNOWLEDGE DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK PONDS FACIAL WASH DI SHOPEE KOTA SURABAYA - Silviana Rahmawati; Supriyono Supriyono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The rapid development of technology requires companies to continuously innovate to ensure their products stand out compared to competitors and align with market demands. This research examines the influence of Product Knowledge and Brand Image on Purchase Decisions for Ponds Facial Wash products on Shopee. The study is quantitative in nature, employing non-probability sampling and purposive sampling techniques for sample selection. The population in this study consists of residents of Surabaya who have used or purchased Ponds facial wash products through the Shopee application, with a total of 96 respondents. The data analysis technique used is Partial Least Square (PLS). The results of this study indicate that Product Knowledge and Brand Image have a positive and significant influence on Purchase Decisions on Shopee. Keywords: Product Knowledge; Brand Image; Purchase Decision.